АППАРАТНЫЕ ПРОБЛЕМЫ ЭЛЕКТРОБЕЗОПАСНОСТИ ПРИ ЭКСПЛУАТАЦИИ ЭЛЕКТРОТЕХНИЧЕСКИХ КОМПЛЕКСОВ С РЕГУЛИРУЕМЫМИ ЭЛЕКТРОПРИВОДАМИ В РУДНИЧНЫХ УЧАСТКОВЫХ РАСПРЕДЕЛИТЕЛЬНЫХ СЕТЯХ ДО 1200 В - Синчук, О.Н.; Ликаренко, А.Г.; Петриченко, А.А.; Зиманков, P.В.; Шкрабец, Ф.П. (Інститут електродинаміки НАН України, Київ, 2016)
Set forth the author's vision of the structure protection devices against alternative operating leakage current for combined mining distribution networks. Conditions have been given an achievement of minimal normative safety and calculation of its settings according to standards of electrical safety. The measurement functions structural scheme was developed for monitoring and fulfillment of minimal safety conditions for continuous and short time currents passing through the human body. References 6, figures 2.